Planting Site Effects on Early Growth of Pecan Tree Transplants - Lenny Wells; Andrew Sawyer (HortScience, 2022)
Site selection is key to successful establishment of fruit and nut trees. The upland soils on which pecan [Carya illinoinensis (Wangenh.) K. Koch] trees are commonly planted in the southeastern United States consist of sites that have recently been in row crop cultivation or pine or hardwood timber. Anecdotal observation suggests that orchards planted to land converted from cultivated row crop fields tends to result in better tree growth and survival than those on land recently converted from timber plantations or wooded areas. The objective of this experiment was to compare growth of first- through third-leaf pecan trees planted on sites with varying land-use history [row crop cultivation or pine (Pinus spp.) tree production up to the year before planting] and to determine the effects of supplemental addition of phosphorus (P), potassium (K), and zinc (Zn) at planting on the two sites. These results suggest that the soil conditions of sites recently in pine timber production limit the growth and development of pecan trees planted to those sites. These limitations result from soil acidity and an exhaustion of soil nutrients and loss of organic matter on pine sites, making the uptake of nitrogen (N), P, K, and calcium (Ca) challenging during the establishment phase unless soils are improved before planting.